Dopamine D(2) receptor function is compromised in the brain of the methionine sulfoxide reductase A knockout mouse - Oien, Derek B. (2010)
Previous research suggests that brain oxidative stress and altered rodent locomotor behavior are linked. We observed bio-behavioral changes in methionine sulfoxide reductase A knockout mice associated with abnormal dopamine signaling. Compromised ability of these knockout mice to reduce methionine sulfoxide enhances accumulation of sulfoxides in proteins. We examined the dopamine D(2)-receptor function and expression, which has an atypical arrangement and quantity of methionine residues. Indeed, protein expression levels of dopamine D(2)-receptor were higher in knockout mice compared with wild-type. However, the binding of dopamine D(2)-receptor agonist was compromised in the same fractions of knockout mice. Coupling efficiency of dopamine D(2)-receptors to G-proteins was also significantly reduced in knockout mice, supporting the compromised agonist binding. Furthermore, pre-synaptic dopamine release in knockout striatal sections was less responsive than control sections to dopamine D(2)-receptor ligands. Behaviorally, the locomotor activity of knockout mice was less responsive to the inhibitory effect of quinpirole than wild-type mice. Involvement of specific methionine residue oxidation in the dopamine D(2)-receptor third intracellular loop is suggested by in vitro studies. We conclude that ablation of methionine sulfoxide reductase can affect dopamine signaling through altering dopamine D(2)-receptor physiology and may be related to symptoms associated with neurological disorders and diseases.